2004
DOI: 10.1021/jm040134d
|View full text |Cite
|
Sign up to set email alerts
|

Non-Nucleoside Benzimidazole-Based Allosteric Inhibitors of the Hepatitis C Virus NS5B Polymerase:  Inhibition of Subgenomic Hepatitis C Virus RNA Replicons in Huh-7 Cells

Abstract: A previously disclosed series of non-nucleoside allosteric inhibitors of the NS5B polymerase of the hepatitis C virus (HCV) was optimized to yield novel compounds with improved physicochemical properties and activity in cell-based assays. Replacement of ionizable carboxylic acids with neutral substituents in lead compounds produced inhibitors with cellular permeability and antiviral activity in a cell-based assay of subgenomic HCV RNA replication (replicon EC(50) as low as 1.7 microM). The improvement in poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…compound A is a potent inhibitor of NS5B in vitro, the effect on HCV RNA replication in cell culture, as measured with the HCV replicon system (44), was marginal (63% inhibition at 50 M) and attributable to the poor cell permeability accorded by the acid functionalities and net negative charge of the compound (28). In an effort to identify C-5 carboxamide analogues that retained in vitro potency but demonstrated superior cell culture activity, a combinatorial chemistry approach 5 led to the discovery of compound C with an EC 50 in a 72-h replicon assay of 1.1 M. Other benzimidazoles that have demonstrated cell-based inhibition of HCV replicons have a free C-5 carboxylic acid (33), whereas compound C features a distinct C-5 carboxamide extension.…”
Section: Inhibition Of Hcv Replicons and Resistance To Benzimidazole mentioning
confidence: 99%
See 1 more Smart Citation
“…compound A is a potent inhibitor of NS5B in vitro, the effect on HCV RNA replication in cell culture, as measured with the HCV replicon system (44), was marginal (63% inhibition at 50 M) and attributable to the poor cell permeability accorded by the acid functionalities and net negative charge of the compound (28). In an effort to identify C-5 carboxamide analogues that retained in vitro potency but demonstrated superior cell culture activity, a combinatorial chemistry approach 5 led to the discovery of compound C with an EC 50 in a 72-h replicon assay of 1.1 M. Other benzimidazoles that have demonstrated cell-based inhibition of HCV replicons have a free C-5 carboxylic acid (33), whereas compound C features a distinct C-5 carboxamide extension.…”
Section: Inhibition Of Hcv Replicons and Resistance To Benzimidazole mentioning
confidence: 99%
“…Benzimidazole 5-carboxamide inhibitors have also been extensively pursued as HCV NS5B-specific inhibitors (25,(27)(28)(29)(30)35). 3 These compounds inhibit an initiation phase of the reaction, and a modified NS5B polymerase with lower RNA-substrate affinity was used to identify these compounds in a screening campaign (32).…”
mentioning
confidence: 99%
“…In other studies, they also can act as antibacterial agent (Nezhad et al, 2005;Ozden et al, 2005), and showed anthelmintics activity of Trichinella spiralis (Mavrova et al, 2005), anti-inflammatory and analgesic activities (Sondhi et al, 2006) and as inhibitors for the hepatitis B (Li et al, 2006) and C viruses (Beaulieu et al, 2004). Some benzimidazoles were also tested as anti-HIV (Roth et al, 1997;Smith et al, 2003), anticancer agents (Craigo et al, 1999;Rida et al, 2006) and antioxidants (Kus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…So by this idea in view, synthesis of fluorobenzimidazole is the interesting area of research. Interest in benzimidazole containing structure stems not only because of exhibiting broad spectrum of pharmacological activity [3] but also displaying significant activities against several viruses such as casein kinase 2 [4], factor Xa [5], hepatitis C virus [6].…”
Section: Introductionmentioning
confidence: 99%